Caracterizaçao ecogeográfica, morfoagronômica e genético molecular de Medusantha martiussi (Benth) HARLEY & J.F.B PASTORE - Oliveira, Edvan Assis de (2025)
Medusantha martiusii (Benth) Harley & JFP Pastore is a plant species of the Lamiaceae family and is endemic to Brazil. It is a perennial shrub with globose flowers and a characteristic aroma, often found in the semiarid regions of the Caatinga and Cerrado biomes. The species inhabits environments characterized by stress, resulting from high temperatures, strong solar radiation, high evapotranspiration rates, negative water balance, and low-fertility soils, in addition to scarce and irregular rainfall and cyclical droughts. Alfazema de caboclo, as it is known by the communities, has social and economic importance. Tea made from its leaves is widely used to treat sore throats. Pharmacological tests of the essential oil have demonstrated the chemical richness of its constituent compounds, such as cineole, carene, and caryophyllene, with biological activities and cytotoxic and antimicrobial properties. It also acts as an insecticide against the Aedes aegypti mosquito and Bemisia argentifolii (dengue mosquito and fruit fly, respectively). The objective of this study was to characterize populations of Medusantha martiusii (Benth.) Harley & JFB Pastore through ecogeographic analysis of their habitats, morpho- and gronomic evaluation of their accessions, physical and chemical profile of their seeds, and investigation of their genetic and molecular diversity. This study aimed to generate support for the conservation, management, and sustainable use of this species of high phytotherapeutic value located in the state of Bahia, Brazil. Chapter I – ECOGEOGRAPHIC STUDIES AND ESSENTIAL OIL PRODUCTION OF Medusantha martiusii (Benth.) Harley & JFB Pastore (Lamiaceae) – characterized the environment of 18 natural occurrence sites of the species regarding climatic, geographic, and edaphic aspects, as well as essential oil production in these environments. The study indicated that Medusantha martiusii occurs predominantly in semiarid regions with low-fertility soils and a wide range of thermal adaptations, ranging from mountainous regions with high relief to low-altitude regions in climate zones with little and poorly distributed rainfall. The average oil content found was 2.08%, and a strong positive correlation with Fe and a negative correlation with Zn was recorded. Chapter II – MULTISPECTRAL IMAGING AND MULTIVARIATE ANALYSIS IN THE CHARACTERIZATION OF SEEDS OF Medusantha martiusii (Benth) Harley & JFB Pastore - aimed to characterize seeds of 11 populations of this species through the use of X-ray and the multispectral imaging technique. The study indicated that seeds of this species presented heterogeneity, both in physical and chemical aspects, with identification of important differences in size and texture attributes, in addition to indicators of physiological quality, maturity, vigor, and viability. In Chapter III - ISSR MARKERS IN THE GENETIC CHARACTERIZATION OF POPULATIONS OF Medusantha martiusii (Benth) Harley & JFB Pastore - 165 loci were characterized with nine molecular markers. The AMD (América Dourada), UMB (Umburanas), ITU (Ituaçu), MDC (Morro do Chapeu) and SAB (Seabra) populations presented the greatest genetic diversity (Nei and Shannom) while JRB (Jeremoabo) and MRC (Maracás) the lowest. Individuals from the ITU (Ituaçu) and SDE (Saúde) populations are the most genetically similar (0.148) while MRC and JGR (Jaguarari) are the most distant . CHAPTER IV - MORPHOAGRONOMIC CHARACTERIZATION OF GENOTYPES OF Medusantha martiusii (Benth) Harley & JFB Pastore, addresses the phenotypic diversity of 13 populations based on qualitative and quantitative descriptors that can assist in actions of collection and conservation of the species' germplasm. Some descriptors were important for separating the populations into groups based on their similarities and differences, such as leaf area, number of tillers, and leaf dry weight. This topic identified the MRC and ABA populations as having the greatest genetic distances, and MDC and JCB as having the smallest genetic distances, according to the Mahalanobis distance matrix. The genotypes collected in ABA, RDC, JGR, SAB, and CSC exhibit superior agronomic characteristics and are therefore recommended for use in breeding programs.